Globalization and its discontents: Why there's a backlash and how it needs to change - Short, John Rennie (Raw Story Media, 2016)
Globalization is under attack. The electoral victory of Donald Trump, the Brexit vote and the rise of an aggressive nationalism in mainland Europe and around the world are all part of a backlash to globalization.
Keywords: globalization; Donald Trump; brexit; trade; economy